Sex-dependent modulation of T and NK cells and gut microbiome by low sodium diet in patients with primary aldosteronism - Nowotny, Hanna F.; Zheng, Tingting; Seiter, Thomas Marchant; Ju, Jing; Schneider, Holger; Kroiss, Matthias; Sarkis, Anna-Lina; Sturm, Lisa; Britz, Vera; Lechner, Andreas; Potzel, Anne L.; Kunz, Sonja; et al. (Frontiers in Immunology, 2024)
BackgroundHigh dietary sodium intake is a major cardiovascular risk factor and adversely affects blood pressure control. Patients with primary aldosteronism (PA) are at increased cardiovascular risk, even after medical treatment, and high dietary sodium intake is common in these patients. Here, we analyze the impact of a moderate dietary sodium restriction on microbiome composition and immunophenotype in patients with PA.MethodsProspective two-stage clinical trial including two subgroups: 15 treatment-naive PA patients compared to matched normotensive controls; and 31 PA patients on mineralocorticoid receptor antagonist treatment before and three months after sodium restriction. Patients underwent blood pressure measurements, laboratory tests, analysis of peripheral blood mononuclear cells via flow cytometry and microbiome analysis.ResultsWe observed a higher percentage of Tregs in treatment-naive PA patients (p = 0.0303), while the abundance of Bacteroides uniformis was higher in PA patients compared to normotensive controls (p = 0.00027) and the abundance of Lactobacillus species however was higher in the subgroup of normotensive controls (p = 0.0290). Sodium restriction was accompanied by a decrease in pro-inflammatory Tc17 cells in male patients (p = 0.0081, females p = 0.3274). Bacteroides uniformis abundance was higher in female patients (0.01230, p = 0.0016) and decreased upon sodium restriction (0.002309, p = 0.0068).ConclusionDietary sodium restriction in patients with PA modulates the peripheral immune cell composition toward a less inflammatory phenotype. This suggests a potential mechanism by which sodium reduction modulates immune cell composition, leading to blood pressure reduction and positively impacting cardiovascular risk.